PENERAPAN DASHBOARD SYSTEM PENDAPATAN ASLI DAERAH (PAD) SEKTOR PARIWISATA PADA KABUPATEN MOJOKERTO MENGGUNAKAN TABLEAU - Hindrayani, Kartika Maulida; Riyantoko, Prismahardi Aji; Fahrudin, Tresna Maulana (Journal of Computer Science and Technology (JCS-TECH), 2024)
Covid-19 has had an impact on the tourism sector, this is reflected in the Regional Original Income data. Data has a major role in helping to clearly understand trends and societal needs. Data needs to be converted into information for decision making and strategic planning. Business Intelligence is a technique for applying the use of data to support stakeholders in making decisions. Tableau is the tool used in this research. The results show data on popular and less popular tourism objects and then the importance of recording data in order to provide a valid picture and make the right decisions.